Evaluation of risks in air transport - Soušek, Radovan; Šustr, Martin; Fuchs, Pavel; Endrizalová, Eva; Novák, Martin; Müllerová, Jana (International Institute of Informatics and Systemics, 2018)
The risk is a part of air transport and part of every other human activity. Risk can be exactly quantified. Thanks to the exact quantification, risk can be rated in economic level. In comparison with another transport modes, air transport as own specifics features. In the air transport is not possible to use usual procedures for calculation of risk level which are used in railway transport and road transport. This paper describes ways, how the calculation model for transport risk can be modified and how it can be applicated.
Hodnocení rizik v letecké dopravě
Keywords: Air Transport, Critical Infrastrucure, Risk; Letecká doprava, kritická infrastruktura, riziko